The impact of the Arab Literary Personality on the lengthy "Layla and Majnun" by Fuzuli Al-Baghdadi: a comparative study - Gomaa Ibrahim, Shehab; Iskandar, Youssef (Al-Adab Journal, 2021)
The study aims to shed light on the character of the hero and to investigate the impact and influence between Arabic literature on the one hand, and the lengthy " Layla and Majnun " by the poet Fuzuli Al-Baghdadi on the other hand. The research dealt with two main characters, Qais bin Al-Mallouh and Layla Al-Amiriya and what they cast their shadows on the epic of the poet Fuzuli Al-Baghdadi, the study traced the personal lives of these two characters and their material and moral life stages.